Signs and Symptoms of Dry Eye in Keratoconus Patients: A Pilot Study. (2nd November 2015) - Carracedo, Gonzalo; Recchioni, Alberto; Alejandre-Alba, Nicolás; Martin-Gil, Alba; Crooke, Almudena; Morote, Ignacio Jimenez-Alfaro; Pintor, Jesús
Abstract: Purpose : To compare signs and symptoms of dry eye in keratoconus (KC) patients versus healthy subjects. Methods : A total of 15 KC patients (KC group, n = 15 eyes) and 16 healthy subjects (control group, 16 eyes) were enrolled in this study. The Schirmer I test with no anesthetic, tear break-up time (TBUT), corneal staining characteristics, and ocular surface disease index (OSDI) scores were evaluated for both groups. Impression cytology, combined with/scanning laser confocal microscopy (LCM), was performed to evaluate goblet cell density, mucin cloud height (MCH), and goblet cell layer thickness (CLT). Finally, tear concentrations of di-adenosine tetraphosphate (Ap4 A) were assessed. Results were statistically analyzed using Shapiro–Wilk and non-parametric Wilcoxon rank sum tests. Statistical significance was set at p < 0.05. Results : KC patients had lower tear volumes and greater corneal staining than did healthy subjects ( p < 0.05). OSDI scores were 44.96 ± 8.65 and 17.78 ± 6.50 for the KC and control groups, respectively ( p < 0.05). We found no statistically significant differences in TBUT between groups. Impression cytology revealed lower goblet cell densities in KC group patients versus control group subjects (84.88 ± 32.98 and 128.88 ± 50.60 cells/mm, 2 respectively, p < 0.05). There was a statistically significant reduction in MCH and CLT in KC group patients compared with control group subjects. Ap4 A tear concentrations were higher in KC group patients than in control group subjects (2.56 ± 1.10 and 0.15 ± 0.12 µM, respectively, p < 0.05). Conclusions : The parameters evaluated in this study indicate that KC patients suffer greater symptoms of dry eye and greater tear instability, primarily due to the decreased mucin production in their tears, than do healthy patients with no KC